2004
DOI: 10.1111/j.1553-2712.2004.tb01369.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Degree of Emergency Department Overcrowding in Academic Medical Centers: Results of the National ED Overcrowding Study (NEDOCS)

Abstract: Objectives: No single universal definition of emergency department (ED) overcrowding exists. The authors hypothesize that a previously developed site-sampling form for academic ED overcrowding is a valid model to quantify overcrowding in academic institutions and can be used to develop a validated short form that correlates with overcrowding. Methods: A 23-question site-sampling form was designed based on input from academic physicians at eight medical schools representative of academic EDs nationwide. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
160
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(169 citation statements)
references
References 22 publications
1
160
0
4
Order By: Relevance
“…We can only speculate as to whether larger numbers would have led to the effect of ED closure ( p ϭ 0.054) to reach statistical significance. Other observations from the model are consistent with findings by Weiss et al, who found that the number of patients admitted through the ED and ambulance traffic, but not nurse staffing levels, correlate with throughput times (10). Finally, we did not address how long the subjects had been waiting, or perceived they had been waiting, before completing their interview.…”
Section: Limitationssupporting
confidence: 78%
“…We can only speculate as to whether larger numbers would have led to the effect of ED closure ( p ϭ 0.054) to reach statistical significance. Other observations from the model are consistent with findings by Weiss et al, who found that the number of patients admitted through the ED and ambulance traffic, but not nurse staffing levels, correlate with throughput times (10). Finally, we did not address how long the subjects had been waiting, or perceived they had been waiting, before completing their interview.…”
Section: Limitationssupporting
confidence: 78%
“…These include the current number of ED patients, the number of ED beds, the number of inpatient beds, the last door-to-bed time, the longest admit time, and the number of critical care patients in the ED. The corresponding formula, as developed by Weiss et al (2004), is:…”
Section: Ed Overcrowdingmentioning
confidence: 99%
“…Seventy-two percent of patients reported at least one positive PTSD symptom at 30 days (defined as a score of 2 or more on at least one PCL-5 question), and 25% reported clinically significant PTSD symptoms (defined as scored 2 or more on at least one B item [questions 1-5], one C item [questions 6 and 7], two D items [questions [8][9][10][11][12][13][14], or two E items [questions [15][16][17][18][19][20] or a total score greater than 32). 19,20 Among the entire cohort the median (IQR) PCL-5 score was 7 (0 to 30).…”
Section: Resultsmentioning
confidence: 99%
“…For each patient, we also recorded comorbid conditions (i.e., Charlson comorbidity index), 16 presenting vital signs in the ED, severity of illness (i.e., Acute Physiologic Assessment and Chronic Health Evaluation [APACHE] II score), 17 and all therapeutic interventions initiated in the ED, as well as ED length of stay and ED crowding using the National Emergency Department Overcrowding Study (NEDOCS) tool. 18…”
Section: Data Collectionmentioning
confidence: 99%